The Effect of Leadership Style and Employee Motivation on Employee Performance of Pt. Indotoko Pangan Makmur - Marhendra, Adhipa; Wahyuningtyas, Ratri (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the influence of leadership style and employee motivation on employee performance at PT. Indotoko Pangan Makmur. A quantitative approach was used, and data were analyzed through multiple linear regression using SPSS... The results show that leadership style has a significant partial effect on employee performance, with a significance value of (0.000) < ? (0.05) and a regression coefficient of 0.285. This indicates that an increase of one unit in leadership style improves employee performance by 28.5%. Employee motivation also has a significant partial effect, with a significance value of (0.000) < ? (0.05) and a regression coefficient of 0.310. Motivation contributes 31% to employee performance, showing that motivated employees tend to perform better. Simultaneously, leadership style and motivation have a strong relationship with employee performance, with a correlation coefficient (R) of 0.936. These variables contribute 55.1% to performance, while the remaining 44.9% is influenced by other unobserved factors. This study aligns with previous findings that leadership style and motivation significantly impact employee performance. Companies are encouraged to improve leadership and employee motivation to achieve optimal productivity.